Theory for nonlinear conductivity switching in semiconducting organic ferroelectrics - Johann, Till Jonas Frederick; Xie, Weiwei; Roosta, Sara; Elstner, Marcus; Kemerink, Martijn (Physical chemistry, chemical physics, 2024)
In this work, the ferroelectric and semiconducting properties of the organic semiconducting ferroelectric benzotrithiophene tricarboxamide (BTTTA), and especially their nonlinear coupling, are theoretically investigated. BTTTA is an exponent of a small class of semiconducting organic ferroelectrics for which experiments have established a surprising polarization direction dependence of the bulk conductivity at finite fields. First, molecular dynamics (MD) simulations are used to investigate the occurrence and, under the influence of an external electric field, the inversion of the macroscopic electric dipole that forms along the axis of supramolecular columns of BTTTA. The MD results are consistent with the experimentally observed ferroelectric behavior of the material. Building on the MD results, a QM/MM scheme is used to investigate the charge carrier mobility in the quasi-1D BTTTA stacks in the linear and non-linear regimes. Indeed, at finite electric fields, a clear resistance switching effect was observed in the form of a hole mobility that is a factor ∼2 larger for antiparallel orientations of the polarization and field than for a parallel orientation. This phenomenon can be understood as a microscopic ratchet that is based on the non-equilibrium interaction between the (oriented) dipoles and the (direction of the) charge transport.
Gesehen am 10.01.2025